(untitled) (Research, Society and Development, 2022)
The role of the Psychologist in prisons is to accompany the convict to avoid the emergence of any clinical condition of a psychic nature. In view of this, the present study aimed to discuss the work developed by the psychologist in the Brazilian prison system with regard to the resocialization of the convict. In the methodology, bibliographic research was used through a systematic literature review. Data collection was carried out using the Scielo, PubMed, LILACS and Google Scholar databases. Of the 41 works selected from 2017 to 2022, 21 were selected and used in this study. The results showed that the psychologist he must work beyond what is found by the legislation, contributing to the minimization of the damages of the prison and so that the reintegration of the convict is made possible. Furthermore, it was suggested that there be the implementation of courses for psychologists aimed exclusively at theoretical teaching of approach to this public, since there are few professionals available.